British officialdoms’ arguments about Southern Kurdistan at the Cairo Conference - Azeez, Ranjdar Mohammed (Sulaimani Journal for Humanities, 2022)
The records of the British government about its Conference, held at Cairo, is often part of the most significant discussion over reconsidering Cabinet’s policy towards the whole Middle East, at a very critical juncture. The perspectives of major British officials who attended the Conference, therefore was important, to complete the procedure of establishing a new political unit of Iraq and to improve the future Anglo-Iraqi relations. The historians’ work on British official’s role to reconsider British strategy towards the Middle East at Cairo will remain significant to those who study modern Iraq’s early political history. Although there are a considerable number of works that refer to Southern Kurdistan, they do not pay attention to the remarkable concerns of British officials on this matter. The aim of this research, therefore, is to realize how British political and financial position in Iraq emerged the different views amongst British officials in determining the future government of Southern Kurdistan, through looking at the substantial volume of documents, from a number of the most useful Archive records, such as the National Archives, the British Library, the Middle East Centre at St Anton’s College at Oxford University, and the Parliamentary Archives. This study consists of two main sections: the first section investigates the Colonial Office’s consideration at Cairo to whether Southern Kurdistan should be governed by Iraq, or to be separated. The second section addresses how the disturbances in Southern Kurdistan before the conference, influenced the British officials’ recommendation towards Southern Kurdistan, during and after the conference.
Keywords: Cairo Conference; Southern Kurdistan; British policy; British officials